KEARNS-SAYRE SYNDROME MIGHT BE MIXED UP WITH CPEO PLUS - Finsterer, Josef; Mahjoub, Sinda Zarrouk- (Malang Neurology Journal, 2019)
In a recent article, Al Ghamdi presented a 40yo parturient with Kearns-Sayre syndrome (KSS) who had received an implantable cardioverter defibrillator (ICD) because of an AVblock II (Mobitz 2 (2:1)) 11y earlier and underwent caesarean delivery for preeclampsia in local anesthesia with bupivacaine and fentanyl.(1) We have the following comments and concerns.